Reductions in anti-inflammatory gut bacteria are associated with depression in a sample of young adults - Liu, Richard T.; Rowan-Nash, Aislinn D.; Sheehan, Ana E.; Walsh, Rachel F.L.; Sanzari, Christina M.; Korry, Benjamin J.; Belenky, Peter (Brain, behavior, and immunity, 2020)
•Microbiome characteristics were compared in young adults with and without depression.•Phylogenetic diversity of the microbiome is reduced in young adults with depression.•The depressed group has fewer anti-inflammatory bacteria, such as Faecalibacterium.•The magnitudes of many microbiome changes align with symptom severity. We assessed the gut microbiota of 90 American young adults, comparing 43 participants with major depressive disorder (MDD) and 47 healthy controls, and found that the MDD subjects had significantly different gut microbiota compared to the healthy controls at multiple taxonomic levels. At the phylum level, participants with MDD had lower levels of Firmicutes and higher levels of Bacteroidetes, with similar trends in the at the class (Clostridia and Bacteroidia) and order (Clostridiales and Bacteroidales) levels. At the genus level, the MDD group had lower levels of Faecalibacterium and other related members of the family Ruminococcaceae, which was also reduced relative to healthy controls. Additionally, the class Gammaproteobacteria and genus Flavonifractor were enriched in participants with MDD. Accordingly, predicted functional differences between the two groups include a reduced abundance of short-chain fatty acid production pathways in the MDD group. We also demonstrated that the magnitude of taxonomic changes was associated with the severity of depressive symptoms in many cases, and that most changes were present regardless of whether depressed participants were taking psychotropic medications. Overall, our results support a link between MDD and lower levels of anti-inflammatory, butyrate-producing bacteria, and may support a connection between the gut microbiota and the chronic, low-grade inflammation often observed in MDD patients.